Peran BAWASLU Provinsi Jambi dalam Verifikasi Partai Politik Pemilu Tahun 2019 - Zarkasi, A; Rizal, Dimas; Putra, Firmansyah (Jurnal Analisis Sosial Politik, 2019)
The purpose of this study was to determine the role of Jambi provincial Election Supervisory Agency in verifying the political parties participating in the 2019 election. In the implementation of verification of political parties that will be investigated is the completeness of administration, the completeness of the management, starting from the provincial level, district / city level administrators and representation woman. then the existence of each political party's office, so that the verification of political parties goes accordingly. The Election Supervisory Agencyof Jambi in overseeing the verification of political parties in Jambi will determine the determination of political parties that will be declared eligible to participate in the general elections in 2019. This research uses empirical research is that researchers will conduct research directly in the field to see facts directly and then analyzed. The existence of political parties participating in the general election is political parties that have fulfilled the requirements as political parties that will participate in the election, both administrative requirements, party management at the national level, provincial level, district / city level and sub-district and village level. The purpose of this verification monitoring is very important because to ensure that political parties that are verified meet the requirements in accordance with applicable regulations, and for parties that meet the requirements, the party has the right to participate in general elections, and vice versa, if the verification results are found political parties that do not meet the requirements, are not entitled to participate in the 2019 general election. Tujuan penelitian ini adalah untuk mengetahui peran bawaslu provinsi jambi dalam verifikasi terhadap partai politik calon peserta pemilu tahun 2019. Dalam pelaksanaan verifikasi partai politik yang akan diteliti adalah kelengkapan adminitrasi, kelengkapan pengurus, mulai dari, pengurus tingkat provinsi, pengurus tingkat kabupaten/kota serta keterwakilan perempuan. Kemudian keberadaan kantor masing-masing partai politik tersebut, agar pelaksanaan verifikasi partai politik berjalan sebagaimana mestinya. Bawaslu provinsi jambi dalam mengawasi verifikasi partai politik yang ada di provinsi jambi akan menentukan penetapan partai politik yang akan dinyatakan memenuhi syarat untuk ikut dalam pemilihan umum tahun 2019. Penelitian ini menggunakan Penelitian lapangan. Penelitian lapangan yaitu peneliti akan melakukan penelitian secara langsung kelapangan untuk melihat fakta secara langsung kemudian dianalisis. Keberadaan Partai politik yang ikut pemilu adalah partai politik yang telah memenuhi persyaratan sebagai partai politik yang akan ikut dalam pemilu, baik syarat administrasi, kepengurusan partai baik tingkat nasional, tingkat provinsi, tingkat kabupaten/kota dan tingkat kecamatan dan desa. Tujuan dari pengawasan verifikasi ini merupakan hal yang sangat penting karena untuk mamastikan bahwa partai politik yang diverifikasi memenuhi syarat sesuai ketentuan yang berlaku, bagi partai yang memenuhi syarat, maka partai tersebut berhak untuk mengikuti pemilu dan sebaliknya, jika hasil verifikasi yang dilakukan ditemukan partai politik yang tidak memenuhi syarat, maka tidak berhak ikut serta dalam pemilu tahun 2019.